Implementasi Kegiatan Magang 5S untuk Peningkatan Kualitas Produksi Sepatu Bagian Assembly di PT X - Anggresta Putri Pratama (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The study analyzes the implementation of the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) in improving shoe production quality at the Assembly section of PT X through observation, interviews, and documentation. Involving supervisors, production leaders, and operators, the study aimed to assess the impact of 5S on production processes. The results showed that the implementation of 5S successfully created a more organized, cleaner, and standardized work environment. These improvements led to a reduction in potential work errors, increased process efficiency, and the establishment of an employee disciplinary culture. Employees became more aware of maintaining cleanliness and orderliness, which contributed to a smoother workflow and better quality control. The findings align with theories of quality management, organizational behavior, and operations management, demonstrating the benefits of 5S in enhancing operational effectiveness. This study confirms that integrating the 5S method into industrial practices, particularly during internships, is an effective strategy to encourage continuous improvement and enhance production quality in the industry.